On the Existence of Periodic Solutions for Certain Classes of Systems of Differential Equations with Random Pulse Influence - Perestyuk, N. A.; Samoilenko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We establish conditions for the existence of periodic solutions for systems of differential equations with random right-hand side and random pulse influence at fixed times. We consider the case of small pulse perturbation and weakly nonlinear systems.